2014
DOI: 10.1155/2014/152102
|View full text |Cite
|
Sign up to set email alerts
|

Jacobsen Catalyst as a Cytochrome P450 Biomimetic Model for the Metabolism of Monensin A

Abstract: Monensin A is a commercially important natural product isolated from Streptomyces cinnamonensins that is primarily employed to treat coccidiosis. Monensin A selectively complexes and transports sodium cations across lipid membranes and displays a variety of biological properties. In this study, we evaluated the Jacobsen catalyst as a cytochrome P450 biomimetic model to investigate the oxidation of monensin A. Mass spectrometry analysis of the products from these model systems revealed the formation of two prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Examples of this property can be found in literature, where it was able to react with drugs (Leod et al, 2007;Mac Leod et al, 2008) and natural products (De Santis Ferreira et al, 2012;Niehues et al, 2012;Rocha et al, 2014) to confirm or predict metabolism products. Therefore, the biomimetic system using Jacobsen catalyst and H 2 O 2 was successfully applied to obtainment of the non-aromatic oxidation products of GQ-11 in order to bring more evidence for the proposed metabolite structures.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of this property can be found in literature, where it was able to react with drugs (Leod et al, 2007;Mac Leod et al, 2008) and natural products (De Santis Ferreira et al, 2012;Niehues et al, 2012;Rocha et al, 2014) to confirm or predict metabolism products. Therefore, the biomimetic system using Jacobsen catalyst and H 2 O 2 was successfully applied to obtainment of the non-aromatic oxidation products of GQ-11 in order to bring more evidence for the proposed metabolite structures.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidants and catalysts were dissolved in ACN:H 2 O (9:1 v/v) for the reactions, except for PhIO which was dissolved in ACN. All combinations of oxidant, substrate and catalyst were evaluated in catalyst:oxidant:substrate ratios of 1:10:10, 1:20:20 and 1:30:30 (0.1 mM catalyst:1 mM oxidant:1 mM substrate, 0.1 mM catalyst:2 mM oxidant:2 mM substrate and 0.1 mM catalyst:3 mM oxidant:3 mM substrate) . The control reactions involved the absence of a catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Since its development, the Jacobsen catalyst has been used to catalyze oxidation reactions including those of non‐functionalized olefins with enantioselectivity and alcohols . In addition, the Jacobsen catalyst has been used in studies with pharmaceuticals and natural products such as carbamazepine, monesin A, lapachol and grandisin …”
Section: Introductionmentioning
confidence: 99%
“…Metabolism data in chicken showed that parent lasalocid is excreted at about 10% the administered dose with a great number of minor metabolites (each less than 5% the whole [ 14 C] activity) of greater polarity that would likely correspond to mono‐ and multihydroxylated lasalocid (see Section 3.2.2.1). Hydroxylated metabolites of the ionophore antibiotics monensin sodium, salinomycin and narasin have been shown to exert reduced ionophoric activity and therefore much lesser toxicity than the parent compound (Donoho, ; Dimenna et al., ; Rocha et al., ; EFSA FEEDAP Panel, ). It can be reasonably assumed that the same would occur with lasalocid hydroxy‐metabolites.…”
Section: Assessmentmentioning
confidence: 99%